Efek LKS IPA bermuatan keterampilan belajar 4C tema kesehatan pernapasan dan ekskresi kita pada hasil belajar siswa kelas VIII SMPN 7 Padang - Resmila Rahmadhani Putri; Asrizal Asrizal; Desnita Desnita; Silvi Yulia Sari (Universitas Negeri Padang, 2019)
The 2013 curriculum can be seen as a solution to answer the challenges of the 21st century. The Indonesian government has supported to improve student learning outcomes by encouraging 4C skills in schools and integrated science teaching in Junior High School. But the real conditions in the school indicated that the integration of science learning material was still relatively low with an average value of 63.07. In addition, the skills which used were still limited to the science process skills. The average value of student learning outcomes in the knowledge aspect was 40.91 and this average value can be classified into a low category. The solution to this problem was to apply the integrated science student worksheet by integrating the 4C learning skills of our respiratory and excretory theme integrated science teaching. The purpose of this research was to investigate the effects of integrated science student worksheet by integrating 4C learning skills on the our respiratory and excretory theme on the learning outcomes of grade VIII students of SMP 7 Padang. This type of research was a quasi-experiment with a non-equivalent control group with only post test design. The population of this research was all VIII grade students of SMP 7 Padang. The sampling technique used cluster random sampling. The research instrument consisted of an observation sheet for attitude aspect, written test for knowledge aspect, and performance assessment sheet for skills aspect. The research data were analyzed by using descriptive statistics and comparison of two means test. The result of the hypothesis test indicated that there was a significant difference between the learning outcomes of students who use integrated science student worksheet and students who didn’t use it. This means that integrated science student worksheet has given a significant effect on learning outcomes consisting of knowledge, skills, and attitudes of grade VIII students of SMPN 7 Padang at a 95% confidence level. Thus, integrated science student worksheet by integrating the 4C learning skills can be used by science teachers and students in science teaching.